2014
DOI: 10.1016/j.sbi.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Computational approaches to mapping allosteric pathways

Abstract: Allosteric signaling occurs when chemical and/or physical changes at an allosteric site alter the activity of a primary orthosteric site often many Angstroms distant. A number of recently developed computational techniques, including dynamical network analysis, novel topological and molecular dynamics methods, and hybrids of these methods are useful for elucidating allosteric signaling pathways at the atomistic level. No single method prevails as best to identify allosteric signal propagation path(s), rather e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
93
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 55 publications
0
93
1
Order By: Relevance
“…2931 Computational studies are still mostly based on sub-microsecond simulations, or based on contact analysis or elastic network modeling of static crystal structures. 32 Notably, allosteric communication has been assumed to involve evolutionarily conserved 33 or positionally correlated 34 networks of residues. The complementarity of computational and experimental approaches, NMR spectroscopy in particular, in studying allostery can be easily appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…2931 Computational studies are still mostly based on sub-microsecond simulations, or based on contact analysis or elastic network modeling of static crystal structures. 32 Notably, allosteric communication has been assumed to involve evolutionarily conserved 33 or positionally correlated 34 networks of residues. The complementarity of computational and experimental approaches, NMR spectroscopy in particular, in studying allostery can be easily appreciated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, computational studies have been found to be very useful in complementing experiments in elucidating allosteric mechanisms (Elber, 2011; Feher et al, 2014; Rousseau and Schymkowitz, 2005), including algorithms for identifying allosteric networks (Gerek and Ozkan, 2011; Ghosh and Vishveshwara, 2007; Kannan and Vishveshwara, 1999; Sethi et al, 2009; VanWart et al, 2014). In particular, molecular dynamics simulations have revealed two pathways and implicated a strong dynamic component in the allosteric regulation of thrombin by thrombomodulin (Gasper et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PDZ domain has been a classic model system to study single domain allostery without major structural changes (9,15,16) (Fig. 1A).…”
mentioning
confidence: 99%